2020
DOI: 10.1128/aem.03039-19
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Kills Bacterial Spores and Cells Exposed to 222-Nanometer UV Radiation

Abstract: This study examined the microbicidal activity of 222-nm UV radiation (UV222), which is potentially a safer alternative to the 254-nm UV radiation (UV254) that is often used for surface decontamination. Spores and/or growing and stationary-phase cells of Bacillus cereus, Bacillus subtilis, Bacillus thuringiensis, Staphylococcus aureus, and Clostridioides difficile and a herpesvirus were all killed or inactivated by UV222 and at lower fluences than with UV254. B. subtilis spores and cells lacking the major DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…In-vivomouse skin results consistent with prior investigations in a 3-D human skin tissue in vitro model [8] which also presented imperative skin damage after typical UV254 , but none after UV207. The outcome readily interpretable with respect to limited range of 207 nm UV light which cannot pass through the stratum corneum surface layer of mouse or human skin; on the contrary, broad spectrum UVC from a 254 nm germicidal lamp can swiftly pass through the and dermis and epidermis.…”
Section: B Far-uvc For Selective Treatments In Humansupporting
confidence: 87%
See 1 more Smart Citation
“…In-vivomouse skin results consistent with prior investigations in a 3-D human skin tissue in vitro model [8] which also presented imperative skin damage after typical UV254 , but none after UV207. The outcome readily interpretable with respect to limited range of 207 nm UV light which cannot pass through the stratum corneum surface layer of mouse or human skin; on the contrary, broad spectrum UVC from a 254 nm germicidal lamp can swiftly pass through the and dermis and epidermis.…”
Section: B Far-uvc For Selective Treatments In Humansupporting
confidence: 87%
“…In [7], extremely low doses of far-UVC light were competently used to deactivate airborne viruses conveyed by aerosols. By use of 222-nm UV radiation (UV222), [8] investigated that how UV222 eradicates cultivating bacteria and spores, and the factors which are imperative for allowing cells and spores to defy the effects of this radiation. UV222 is theoretically a safer alternate to UV254 which is frequently utilized for surface sanitization.…”
Section: Related Workmentioning
confidence: 99%
“…2016; Taylor et al . 2020). Spore purification included centrifugation through 50 and 45% Histodenz solutions for CaDPA‐replete and CaDPA‐less spores, respectively, as described above; the yields of purified spores of the different C. difficile different strains were all ~7 × 10 8 spores from each plate.…”
Section: Methodsmentioning
confidence: 99%
“…However, 10 µl aliquots of dilutions were applied in a grid in an anaerobic cabinet to prereduced brain heart infusion agar plates containing 1·9 mmol l −1 taurocholic acid (TA) and 1 g l −1 l ‐cysteine as described (Taylor et al . 2020). These plates were incubated at 37°C in an anaerobic cabinet with a gas of 85% N 2 , 5% CO 2 and 10% H 2 until no more colonies appeared (14–24 h) and colonies were counted.…”
Section: Methodsmentioning
confidence: 99%
“…This last study concluded that low-intensity levels equivalent to 2 mJ cm −2 of UV-C 222-nm on the center of the irradiation target in public locations might represent a safe and efficient methodology for limiting the transmission and spread of airborne-mediated microbial diseases. This same UV-C 222-nm fluence was demonstrated to produce enough DNA damage to kill B. subtilis endospores [ 26 ]. Although this particular study also reported skin damage after typical UV-C 254-nm , none after UV-C 207-nm [ 26 ], our robots were designed to be used exclusively in the absence of people, and the sweeping of the entire room by the robot achieved a cumulative effect of additional radiation in successive passes.…”
Section: Discussionmentioning
confidence: 99%